Creativity for employment & business opportunity : an entrepreneurship manual for young people in CARICOM (Caribbean Community Secretariat GeorgetownGY, 2014)
Presents a tool to engage and inspire young people in and out of school and from all walks of life to run successful businesses that generate income and contribute to the goals of national and regional development.
Keywords: ENTREPRENEURSHIP